Modeling and simulation of closed low-pressure zeolite adsorbers for thermal energy storage. (August 2019) - Schaefer, M.; Thess, A.
Highlights: A two-dimensional general model for closed low-pressure adsorbers is presented. Different adsorbent configurations (powder, granules and honeycomb) are studied. For granules and honeycomb adsorbents temperature waves are observed. Equilibrium cannot be assumed and the rarefaction slip effect should be considered. An optimum of the thermal performance over the channel or particle size is found. Abstract: Thermal energy storages are essential for the efficient implementation of renewable energy sources. Therefore, thermal energy storages based on closed adsorption are studied in literature. Against this background, closed low-pressure adsorbers with zeolite 13X adsorbent of varying configuration (powder, granules, honeycomb) are modeled, simulated and compared in this work. The focus is on the discharging process of the adsorber and special emphasis is put on the accurate incorporation of the rarefaction effects, resulting from low pressure. The simulation results reveal similar behavior for honeycomb and granules adsorbents (temperature wave), while a qualitatively different behavior is observed for the powder adsorbent case. The different behavior for the powder adsorbent case results from a modification of the vapor supply. With respect to modeling, it is found that equilibrium assumptions can not be applied in general. Only for the case of powder adsorbent it is valid to neglect the intra-particle mass transfer resistance and assume instant adsorption equilibrium. Furthermore, rarefaction effects are found to be relevant only for small channel and particle diameters d c / p ⩽ 1 mm . Regarding the application, the discharging performance in terms of a defined discharging degree is strongly influenced by the channel and particle diameter. An optimum channel and particle diameter respectively for the honeycomb and granules adsorbent is determined with an maximum discharging degree of 80%. The optimum is a result of limitations by inter- and intra-particle mass transfer resistances. Finally, the discharging degree also strongly depends on the discharging conditions and decreases with increasing discharging temperature and increasing volume flow of the heat transfer fluid.